Pistachio (Pistacia vera) by-products as ruminant feed: a review on production, management and utilization in arid and semi-arid areas in the Middle East - Alkhtib, Ashraf; Wamatu, Jane; Kaysi, Yahya; Mona, M.; Rischkowsky, Barbara A. (Journal of Experimental Biology and Agricultural Sciences, 2017)
This review presents recent knowledge of the inclusion of pistachio by-products in diets of ruminants.Pistachio harvesting and processing result in considerable amounts of by-products which include hulls (the outer cover of fruit), woody shells (mesocarp), blank fruits, clusters (sometimes referred as twigs) and leaves.The by-products can be preserved by natural drying or ensilaging.This review evaluates pistachio by-products in terms of chemical composition, nutritive value and their effects on ruminant performance and product quality.Their nutritive value is affected by factors which include type of byproduct, pistachio variety, harvesting time and preservation method.Pistachio by-products can use as a source of protein and energy in ruminant feeding to support maintenance and production of meat, milk, wood and hair.Their replacement value in diets of growing, fattening and lactating ruminants ranges between 21-35%.The replacement values of silage from pistachio by-products ranges between 15-24%.However, the presence of high levels of copper and phenolic compounds in pistachio by-products may restrict their inclusion in high proportions into ruminant diets.There is need for more research on the inactivation of phenolic compounds in pistachio by-products so that they can be fed to ruminants in larger proportions.Further studies are needed to evaluate the effects of pistachio by-products on production and reproduction performance of ruminants as well as product quality.The presence of pesticides, fungicides and phenolic compounds in pistachio by-products necessitate identifying the effect of long term feeding on livestock health.